Eventos centinela materno como factores predictivos del sufrimiento fetal en el Hospital General Guasmo Sur. - Acurio Jara, Marilyn Michelle (2023)
Sentinel events are considered to be the unexpected event that causes death, or serious physical or psychological injury. This assesses all clinical events that act as significant indicators for maternal and fetal health, which alerts fetal suffering because it is considered a problem. At the hospital level, it is considered an abnormal complication of fetal heart rate, due to decreased heartbeats. The general objective of this research was to determine the maternal sentinel events that predict fetal distress in patients admitted to the Guasmo Sur General Hospital. The research method used to develop this research was inductive with a transversal quantitative modality - retrospective, the technique was based on observation and data collection obtained from the statistics database of the Guasmo Sur General Hospital. Consisting of a population of 100 pregnant patients who were admitted to the hospitalization area, using inclusion and exclusion criteria, a total of 100 pregnant women who presented fetal distress were obtained. It was concluded that the incidence of maternal risk factors such as preeclampsia is 48%, which is a high percentage and had a higher prevalence between weeks 33 to 36 of gestation.